Tren Penggunaan Telemedicine Sebagai Solusi Awal Pelayanan Kesehatan Pada Masa Pandemi Covid-19 di Indonesia - Dian Paramitha Asyari (JUKEJ : Jurnal Kesehatan Jompa, 2022)
Abstract Telemedicine services are increasingly in demand by people in Indonesia since the Covid-19 Pandemic. This is because many people want treatment but the situation does not allow them to come directly to the Health Service. As a result, a number of Telemedicine services are growing in Indonesia with various online service features. A number of government-owned health facilities have also switched to online platforms since the pandemic. The purpose of this study is to see an overview of the use of Telemedicine in Indonesia as an initial solution for health services during the Covid-19 Pandemic. This study uses a qualitative analysis of several telemedicine platforms that already exist in Indonesia and compares the trends in their use before and during the Covid-19 pandemic. The results of the analysis showed that there was an increasing trend of using Telemedicine in Indonesia as the first step for online health services before people came to health facilities for further treatment. Keywords : Telemedicine, Health Service, Covid-19